Microsomal Prostaglandin E Synthase-1 Expression in Inflammatory Conditions Is Downregulated by Dexamethasone: Seminal Role of the Regulatory Phosphatase MKP-1 - Tuure, Lauri; Hämäläinen, Mari; Whittle, Brendan J.; Moilanen, Eeva (Frontiers in Pharmacology, 2017)
Microsomal prostaglandin E synthase-1 (mPGES-1) is an inducible enzyme situated downstream of cyclo-oxygenase-2, promoting the excessive PGE2 production in inflammation. Dexamethasone is known to suppress mPGES-1 but the mechanisms regulating mPGES-1 expression remain poorly known. MKP-1 is a phosphatase controlling the proinflammatory MAP kinase pathways p38 and JNK, thus limiting the inflammatory responses. We have now investigated the role of MKP-1 and MAP kinases p38 and JNK in the regulation of mPGES-1 expression by dexamethasone. Dexamethasone increased MKP-1 and decreased mPGES-1 expression in J774 macrophages and in peritoneal macrophages from wild-type but not from MKP-1 deficient mice. Dexamethasone also reduced p38 and JNK phosphorylation along with enhancement of MKP-1, while inhibition of JNK reduced mPGES-1 expression. These findings were also translated to in vivo conditions as dexamethasone downregulated mPGES-1 expression in paw inflammation in wild-type but not in MKP-1 deficient mice. In conclusion, dexamethasone was found to downregulate mPGES-1 expression through enhanced MKP-1 expression and reduced JNK phosphorylation in inflammatory conditions. The results extend the understanding on the regulation of mPGES-1 expression and highlight the potential of MKP-1 as an anti-inflammatory drug target.